Derivation and Inflection Inaccuracies: A Morphological Error Matrix for Improving Arabic Writing Competence in the Pesantren Context - Setiyadi, Alif Cahya; Najib, Ahmad Farhan Rif'an; Mahmudi, Ihwan; Malik, Muhammad Khoirul (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2025)
This study aims to identify and analyze morphological errors found in students’ weekly insha’ writings within the Pesantren (Islamic boarding school) environment. These errors, especially in derivation (ishtiqāq) and verb conjugation (taṣrīf), indicate limited consolidation of essential sharf principles. Despite the consistent implementation of weekly insha’ activities, dominant error patterns persist, revealing a gap between morphological theory and actual language use. Data were collected from students’ written works, semi-structured interviews with teachers and learners, and classroom observations to capture the teaching learning context. A qualitative content analysis was applied using a deductive-inductive coding process to classify errors into categories such as incorrect fi‘l forms, wazn inconsistencies, and misuse of ism patterns violating sharf rules. A morphological error-tracking matrix was designed to map and interpret these morphological deviations systematically. The findings demonstrate that limited contextual reinforcement and lack of applied practice contribute to recurring errors. Consequently, this study highlights the need to reorient sharf instruction toward integrative and practice-based approaches, with the morphological error-tracking matrix serving as both diagnostic and pedagogical innovation.